Informatization of raw materials extraction and processing looking forward to the XXI century - Rybár Pavol; Podlubný Igor; Kotial Imrich (Acta Montanistica Slovaca, 2002)
The notion of informatization of processes is introduced, and the difference between informatics and informatization is explained and emphasized. The mission of informatization is specified, as well as the process of its realization in the form of growing penetration of all industrial branches including raw materials extraction and processing. The notions of stages and levels of informatization are defined, which allows comparison of current state and formulation of visions and plans for the future. It is demonstrated that efficient informatization would be impossible without preparation of specialists for informatization of each application field. The tasks for development of informatization are defined, especially in the field of education, research and applications.